The impact of work-life balance, work safety, and workload on employee retention in Indonesia's port industry - Jennifer Collin Suprapto; Puput Marshanda; Betric Nandela, Fransisca; Siddiq , Dedi Muhammad (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study is to examine how employee retention in Indonesian ports is impacted by workload, work-life balance, and safety. The study makes use of primary data and a quantitative methodology. The study's 200 participants are Pelabuhan Indonesia employees. Saturated samples, or sampling strategies that use the entire population as a sample, are the method used in this study. Questionnaires are used to collect data. According to the study's findings, (1) workload is somewhat positively correlated with employee retention (tcalculate > ttable), meaning that (3.261 > 1.65259), with a significance level of 0.01. (2) With a significance level of 0.012, partial work balance has a positive impact on employee retention (tcount > ttable), resulting in (2.533 > 1.6529). (3) There is a partial positive relationship between work safety and employee retention (tcalculate > ttable), resulting in (2.414 > 1.6529) with a significance level of 0.017. (4) Employee retention (Fhitung>Ftabel), or (10.261 > 3.04), is influenced (simultaneously) by workload, work balance, and work safety, with a significance level of 0.000 < 0.05. Based on the research findings, it can be inferred that the workload variable positively affects employee retention in the Port of Indonesia company, as does work balance